2021
DOI: 10.1021/acs.analchem.1c01500
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and C2–C6 Alkane Sensing in Complex Fuel Gas Mixtures with Fiber-Enhanced Raman Spectroscopy

Abstract: Power-to-gas is a heavily discussed option to store surplus electricity from renewable sources. Part of the generated hydrogen could be fed into the gas grid and lead to fluctuations in the composition of the fuel gas. Consequently, both operators of transmission networks and end users would need to frequently monitor the gas to ensure safety as well as optimal and stable operation. Currently, gas chromatography-based analysis methods are the state of the art. However, these methods have several downsides for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 69 publications
0
49
0
Order By: Relevance
“…The detection capability of the Raman system was validated by the detection experiment of gas samples with critical concentrations. Experimental results showed that this system can be used in fields of trace gas detection in ppm level; this better LODs compared with the recent results [18,24] on fuel gas mixtures (hydrocarbons, air constituents, as well as H 2 S) from HC-ARFs might be the contribution of collection of forward Raman scattering and the digital spatial filtering of an imaging spectrograph. The spectral resolution and detection range of our homemade imaging spectrograph allowed the simultaneous detection of multiple gases.…”
Section: Verification Of the Detection Capability Of The Systemmentioning
confidence: 67%
See 2 more Smart Citations
“…The detection capability of the Raman system was validated by the detection experiment of gas samples with critical concentrations. Experimental results showed that this system can be used in fields of trace gas detection in ppm level; this better LODs compared with the recent results [18,24] on fuel gas mixtures (hydrocarbons, air constituents, as well as H 2 S) from HC-ARFs might be the contribution of collection of forward Raman scattering and the digital spatial filtering of an imaging spectrograph. The spectral resolution and detection range of our homemade imaging spectrograph allowed the simultaneous detection of multiple gases.…”
Section: Verification Of the Detection Capability Of The Systemmentioning
confidence: 67%
“…At present, several signal-enhancing devices have been proved to be effective: passively locked cavities, [1][2][3][4] where the work of Ohara et al showed a limit of detection (LOD) of 100 ppm for methane with 1-s exposure time and 40-W intra-cavity power, [2] and the work of Frosch et al showed a signal enhancement of 6 orders of magnitude [3] as well as LODs between 150 and 350 ppm in the process monitoring of biogas production [4] ; actively locked cavities, [5][6][7] where Hippler's work arrived a LOD of 1 mbar in 1 bar of total pressure (1000 ppm) with a diode laser of 10 mW and integration time of 30 s [5] ; multipass cells, [8][9][10] where the work of Velez et al recorded a LOD of methane below 1 ppm with a multi-mode diode laser of 6 W and exposure time of 5 s [10] ; functionalized waveguides, where the work of Holmstrom et al showed an enhancement over 9 orders of magnitude with a strong dependence on analytes [11] ; and hollowcore fibers (HCFs). [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among these, HCF is an excellent component, which can be used not only as gas sample cells with long optical path but also as effective collectors of Raman radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations of Raman spectra of polyatomic molecules are rather complicated and always require verification with experimental data. According to the data of Knebl et al, 12 among the given characteristic peaks of ethane (993 cm −1 ), propane (869 cm −1 ), n-butane (830 cm −1 ), isobutane (798 cm −1 ), n-pentane (840 cm −1 ), isopentane (765 cm −1 ), and nhexane (1038 cm −1 ), only the peaks of n-butane and n-pentane are overlapped. Based on this, it can be concluded that the concentrations can be estimated by using the peak or integral intensities of the indicated bands without taking into account the overlap with the spectra of other components.…”
mentioning
confidence: 99%
“…In addition, these tables contain data for methane, carbon dioxide, and nitrogen (at 1 atm). Note that the peak at 1038 cm −1 chosen by Knebl et al 12 for the estimates of n-hexane concentration is not the best choice. According to Figure 1, the n-hexane peak is located at 1040 cm −1 and it is overlapped by more intense bands of n-pentane and isopentane with a maxima at 1038 cm −1 as well as the rotational S 3 line of hydrogen (1035 cm −1 ).…”
mentioning
confidence: 99%